Pemberdayaan Ekonomi Rakyat melalui UKM dan Entrepreneurship di Kalangan Pengusaha Kecil - TW, Hg. Suseno (Fakutas Ekonomi Unika Widya Mandala Surabaya, 2003)
As the crisis deepened in 1997 and early 1998, there were fears that many workers in several sectors would become unemployed and numbers of poverty had increased. Urban unemployment had risen from 8 to 9,3%, and rural unemployment from 2,8 to 3,3% in 1999. What is happening in the Indonesian economy at present? There were caused the people power are not focus in the economic policy. As Warren Buffet said, when the tide goes ou4 that you can see who's swimming naked. This article will to discuss about the power of people's economy. How to correlation between people's economy concept and small-medium enterprise, and to improve entrepreneurship in small-medium enterprises.